Intra-rater and inter-rater reliability of cranio cervical flexion test in symptomatic subjects of neck pain using pressure biofeedback - Rajalaxmi, V; Kotteswari, S; Nisha, R Nithya; Nallathambi, Mohan (Bangladesh Journal of Medical Science, 2023)
Objective: To investigate the intra – rater and inter – rater reliability of cranio cervical flexion test in symptomatic subjects. Background of study: Neck flexor muscles endurance was negatively correlated with cervical pain and dysfunction. Cranio cervical flexion test protocol has been advocated to train cranio cervical flexor muscle performance at present there is no consensus to the most effective method. The CCFT is a clinical test of neuromotor control of deep flexor of the cervical spine. Methodology: This was an observational study design with test-retest type and conducted in the ACS medical college and hospital. 50 samples were selected based on inclusion criteria. The CCFT was measured by one tester twice for intra rater reliability and two testers for inter-rater reliability were again tested after 24 Hours (Next day) by keeping time and environment optimal. In this CCFT, the activation pressure score and highest-pressure score was measured using Pressure Biofeedback unit. Result: The mean score for Activation Pressure by intra-rater tester one was found to be 2.24 (1.69) and 2.64 (1.48) in retest. The ICC intrarater score for Highest pressure value by tester one was 23.92 (2.17) and 24.32 (1.99) in retest. The mean score for activation pressure by Inter – rater examiners was found to be 2.92(1.15) by examiner - 1 and 2.72(1.19) by examiner - 2. The ICC Inter – rater score for highest pressure value by examiner - 1 was 24.32(1.95) and 24.4(2.33) by examiner - 2. The ICC value of the study indicated high reliability of the activation pressure and highest-pressure value among the intra and inter-raters. Conclusion: The CCFT has high inter-rater and intra-rater reliabilities in symptomatic subjects. Bangladesh Journal of Medical Science Vol. 22 No. 03 July’23 Page : 617-622